Relações Públicas e o processo de análise de cenários - Scarpelli, Vitor Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper, result of a bibliographic review, documentary research and interview with a professional of public relations area (PR), presents a scenario analysis tool and the way how the public relations professional can use it. Are pointed some abilities and strategic skills of this professional that can actually enable him to the prospection, building and analyze of scenarios, from the perspective of relationship with the organization publics. The scenario analysis tool is a strategic way to make some decisions, being used to the analysis of junctures, that can back up organizations' actions and activities, considering possible future results, in other words, the consequences and the developments caused by certain organization attitude or stance. On the end of this paper, we present a propose of strategic plan to Public Relations, using a suggested use for the tool

Este trabalho, resultado de revisão bibliográfica, pesquisa documental e entrevista com profissional da área de Relações Públicas (RP), apresenta a ferramenta de análise de cenários e a maneira como o profissional de RP pode utilizá-la. São apontadas algumas habilidades e competências estratégicas deste profissional que o capacitam para a prospecção, construção e análise de cenários sob a ótica de relacionamento com os públicos das organizações. A ferramenta de análise de cenários é uma forma estratégica de tomada de decisões, sendo utilizada para análise de conjunturas que possam respaldar ações e atividades organizacionais, considerando os possíveis resultados futuros, ou seja, as consequências e desdobramentos ocasionados por determinada atitude ou postura da organização. No final deste trabalho apresentamos uma proposta de planejamento estratégico para as Relações Públicas, utilizando uma sugestão de uso da ferramenta
Keywords: Desenvolvimento organizacional - Administração; Relações publicas; Estrategia; Planejamento estrategico; Clima organizacional; Organizational change Management